<p>^I don’t have the BB so I can’t help you there (although, h(1)=g(2*1)+2=g(2)+2. Presumably you know g(2), right?).</p>
<p>Anyways, functions. They are really an input-output machine. You input a value (generally, but not always, x). You output another value (generally, but not always, f(x) or, in other words, y). The function defines what one does to the input to get the output. Almost every graph you’ve seen is a function. This is true because you input your x value and output a y value. Using notation like f(x) is just a way to generalize functions when there is no graph. </p>
<p>Anyways, if your function is f(x)=3x+5 (which can generally also be written as y=3x+5), that means that you take any x input value, multiply it by 3, and add 5 to get your output f(x). So, f(2)=3*2+5=11. Here, your input is 2, and your output is 11. If you were to graph this, x would be your x-axis and f(x) would be your y-axis, so you’d have the point (2,11). To give you a similar function, g(a)=a^2-4 (remember, function inputs do not always have to be x and function outputs do not have to be f(x)). in this case, a is your input and g(a) is your output. g(a) is like f(a), except you are only using different letters. If you already have a function f(a), then your second, different, function can not be f(a) because that is a contradiction, as two different things can’t be represented by the same letters. So, you commonly use g to denote a second function, and h a third function, and so on. Anyways, if you input an a value of 0, so g(0)=0^2-4=-4, you get an output of -4. If you input an a value of 2, so g(2)=2^2-4=0, you get an output of 0. If you were to graph this, a would replace the x-axis and g(a) would replace the y-axis. You’d have the points (0,-4) and (2,0). </p>
<p>So, when you have two functions, like in your problem, you have to find two things. So, say you have a function f(a)=g(a^2)+5 and g(b)=3b. Say a=2. So, f(2)=g(4)+5. But, we need to know g(4) to solve the problem. Luckily, we know g(b)=3b. So, g(4)=3*4=12. Substituting that back in, we get f(2)=12+5=17. </p>
<p>Likewise, say you have a function h(r)=2<em>f(g(r)), where g(r)=3r+2 and f(s)=s^2. So, find h(3). h(3)=2</em>f(g(3)). g(3)=3<em>3+2=11 (because g(r)=3r+2). So, h(3)=2</em>f(g(3))=2<em>f(11). f(11)=11^2=121 (because f(s)=s^2). So, h(3)=2</em>f(11)=2<em>121=242. You could do this a more direct way by plugging the g function straight into the f function. In other words, h(r)=2</em>((3r+2)^2) by substituting 3r+2 in for g(r) (which is also s, when you think about it) and s^2 in for f(s). So, h(3)=2<em>((3</em>3+2)^2)=2<em>((11)^2)=2</em>121=242. Same answer. </p>
<p>^When it comes down to it, functions are really about book-keeping, especially when you have multiple functions in one problem. Even in problems with just one function, you have to sort the inputs from the outputs.</p>